Two-Stage Revision Anterior Cruciate Ligament Reconstruction: A Systematic Review of Bone Graft Options for Tunnel Augmentation. Issue 3 (March 2020) - Salem, Hytham S.; Axibal, Derek P.; Wolcott, Michelle L.; Vidal, Armando F.; McCarty, Eric C.; Bravman, Jonathan T.; Frank, Rachel M.
Background: No consensus is available regarding the optimal choice of bone graft material for bone tunnel augmentation in revision anterior cruciate ligament (ACL) surgery. Purpose: To compare the outcomes of different bone graft materials for staged revision ACL reconstruction. Study design: Systematic review. Methods: A systematic review using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines was performed. PubMed, EMBASE, and the Cochrane Library were queried through use of the terms anterior cruciate ligament and revision to identify all studies reporting outcomes of bone tunnel grafting in 2-stage revision ACL reconstruction. Data extracted included indications for 2-stage surgery, surgical technique, graft material, time between surgeries, rehabilitation protocols, physical examination findings, patient-reported outcomes, and radiographic and histologic findings. Results: The analysis included 7 studies with a total of 234 patients. The primary outcome in 2 studies was graft incorporation (mean follow-up, 8.8 months), whereas the other 5 studies reported clinical outcomes with follow-up mean ± SD of 4.2 ± 2.1 years. The indication for bone grafting and between-stage protocol varied among studies. Autograft was used in 4 studies: iliac crest bone autograft (ICBG, n = 3) and tibial bone autograft (TBA, n = 1). In 2 studies, the authors investigated the outcomes of allograft: allograft bone matrix (ABM) and allograft bone chips (AC). Finally, 1 study compared ICBG to a synthetic bone substitute. Radiographic evaluation of bone graft integration after the first stage was reported in 4 studies, with an average duration of 4.9 months. In 4 studies, the authors reported the time interval between first and second surgeries, with an average of 6.1 months for ICBG compared with 8.7 months for allogenic and synthetic grafts. Revision ACL graft failure rates were reported by 5 studies, including 1 study with ABM (6.1%), 1 study with AC (8.3%), 1 study with TBA (0%), and 2 studies with ICBG (0% and 2%). Conclusion: The indications for staged ACL reconstruction and the rehabilitation protocol between stages need to be clearly established. The available data indicate that autograft for bone tunnel grafting in 2-stage ACL revision may be associated with a lower risk of revision ACL reconstruction graft failure compared with allograft bone.